Chiral catalysts derived from biomass: design, synthesis and applications in asymmetric catalysis. Issue 6 (8th January 2020) - Ngo, Thi Thuy Duong; Huynh, Khanh Duy; Ibrahim, Houssein; Nguyen, Thi Huong; Bournaud, Chloée; Toffano, Martial; Vo‐Thanh, Giang
Abstract: The development of new and more efficient catalytic systems is the subject of increasing attention from both academic and industrial research. Moreover, biomass is an endless supply of hydrocarbon materials that can be used as renewable raw materials for the development of new organic compounds. In this context, many research groups have devoted their works to products with a natural chirality source, non‐toxic, biodegradable and usually cost effective for the development of new chiral catalysts. Some new chiral molecules derived from biomass such as carbohydrates and natural amino acids have been synthesized and used as chiral ligands or organocatalysts for asymmetric transformations leading to the formation of expected products in good yields with high enantioselectivities